Mesoporous carbon microspheres with high capacitive performances for supercapacitors. (10th March 2015) - Li, Zesheng; Li, Dehao; Liu, Zhenghui; Li, Bolin; Ge, Chunyu; Fang, Yueping
Highlights: Small mesopores-enriched porous carbon microspheres were easily synthesized. Small mesopores offer high ion-accessible surface area and facilitated ion diffusion. The porous carbon exhibited a high specific capacitance and a good power property. Abstract: Novel small-mesopores-enriched porous carbon microspheres have been synthesized from carbonaceous polysaccharide microspheres, by using the associated lithium acetate treating and heat treating strategies. X-ray diffraction, scanning electron microscope, transmission electron microscopy and nitrogen adsorption-desorption techniques have been employed to investigate the as-prepared samples. The analysis results indicate that the porous carbon microspheres has a high specific surface area of 1163 m 2  g −1 and a satisfactory small mesoporous texture (2∼5 nm), with the mean pore size of 3.24 nm and the pore volume ratio of 2∼5 nm pores up to 92%. The capacitive performances of the samples in 6 mol L −1 KOH aqueous electrolyte, have been tested by cyclic voltammetry, electrochemical impedance spectroscopy and charge-discharge techniques. A specific capacitance of 171.5 F/g is obtained for the porous carbon microspheres via charge-discharge at a current density of 1000 mA/g. It also displayed a very high cycle stability of 97.8%, compared with the initial capacitance, after 1000 cycles at the high current density of 1000 mA/g.